Assessing Student Stress Across Admissions Models: Mixed-Methods Evidence Comparing Portfolio and Standardized Testing Systems in Malaysia and China - Hu , Xiyue; Zainudin, Zaheril (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study investigates differences in exam-related stress among art undergraduates in China and Malaysia, representing two distinct admissions systems: standardized testing and portfolio-based review. Using a mixed-methods approach, quantitative data from 412 students (China: n = 207; Malaysia: n = 205) were triangulated with qualitative insights from semi-structured teacher interviews. Results revealed that Chinese students reported significantly higher stress levels (M = 3.45, SD = 0.55) compared to Malaysian students (M = 3.14, SD = 0.40), with an independent-samples t-test confirming this difference (t (410) = 6.51, p < .001). Psychometric indicators demonstrated strong internal consistency (Cronbach’s α ≥ .70) and sampling adequacy (KMO = .940, Bartlett’s χ² = 3704.466, p < .001), supporting the reliability of the measures. Thematic analysis of interview data further contextualized the findings: Chinese educators highlighted exam-oriented pressures and ambiguous grading standards as primary stressors, whereas Malaysian educators emphasized that portfolio assessments, while demanding, promote autonomy and self-expression. Collectively, the results suggest that assessment design—not merely difficulty—modulates the intensity and nature of academic stress. Integrating process-oriented elements, such as formative feedback or reflective documentation, within standardized frameworks could reduce exam anxiety without compromising academic rigor. The findings provide practical implications for admissions reform and psychological well-being in higher art education across diverse cultural contexts.